2007
DOI: 10.1002/pat.1025
|View full text |Cite
|
Sign up to set email alerts
|

Study the effect of inorganic salts on the chemically polymerized aniline films using quartz crystal microbalance

Abstract: The chemical oxidation of aniline with ammonium peroxydisulfate to form polyaniline (PANI) films has been studied in different aqueous acid mediums such as HCl, HNO 3 , and H 2 SO 4 . The yield and the growth rate of the PANI film deposition were measured using the quartz crystal microbalance (QCM) technique. The effect of different salts such as KCl, NaNO 3 , and K 2 SO 4 and their concentration on the yield and the growth rate of the film formation are investigated. The yield of PANI film deposition depends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…This would convert some of the sulfonate groups to sulfonic acid. Some literatures have also suggested that the number of structural defects during polymerization can be reduced by lowering temperature of its reaction (Ayad and Rehab, 2008). They found that this slowed the polymerization growth rate which reduced the number of structural defects in the CP oligomers.…”
Section: Sheet Resistance and Conductivity Of The Fabricated Eapmentioning
confidence: 99%
“…This would convert some of the sulfonate groups to sulfonic acid. Some literatures have also suggested that the number of structural defects during polymerization can be reduced by lowering temperature of its reaction (Ayad and Rehab, 2008). They found that this slowed the polymerization growth rate which reduced the number of structural defects in the CP oligomers.…”
Section: Sheet Resistance and Conductivity Of The Fabricated Eapmentioning
confidence: 99%